Constituents of Boesenbergia pandurata (syn. Kaempferia pandurata). III Isolation and Synthesis of (±)-Boesenbergin B - Chulabhorn Mahidol (2018)
A new chalcone derivative (±)-boesenbergin B and the known (±)-panduratin A have been isolated from Boesenbergia pandurata Schl. (syn. Kaempferia pandurata Roxb.; family Zingiberaceae). Spectroscopic studies have established the structure (±)-(E)-l-[5′-hydroxy-7′-methoxy-2′-methyl- 2′-(4″-methylpent-3″-enyl)-2″H-l-benzopyran-6″-yl]-3-phenylprop-2-en-l-one for boesenbergin B. A simple synthesis of boesenbergin B has been achieved and its acid-catalysed cyclization has been studied. © 1984 ASEG.